The Women's book of racquetball - Wright, Shannon; Keeley, Steve (Chicago : Contemporary Books, 1980)
You are going to learn racquetball from this book like you've never learned it before. The reason? Well, there are two reasons, and their names are Shannon Wright and Steve Keeley. Shannon is the best female player in the history of the game. She won the 1977 and 1978 national singles championships and is the NRC professional tour's all-time top female money winner. When people talk about women's racquetball, you know they're talking about Shannon Wright. And everyone who has taken a racquet into hand with purpose has heard of Shannon's co-author, Steve Keeley. Steve has been one of the top male professionals since l established racquetball's first pro tour in 1973.Perhaps more significant to you, he is the most respected instructor and author in the sport.
1. The Game -- 2. Equipment -- 3. Coordination Drills and Warm-Ups -- 4. Forehand Grip -- 5. Forehand Stroke -- 6. Backhand Grip -- 7. Backhand Stroke -- 8. Stroke: Common Errors and Pointers -- 9. Practice.
Includes index.
Keywords: RACQUETBALL